1-3y=2(y-8)

Simple and best practice solution for 1-3y=2(y-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-3y=2(y-8) equation:


Simplifying
1 + -3y = 2(y + -8)
Reorder the terms:
1 + -3y = 2(-8 + y)
1 + -3y = (-8 * 2 + y * 2)
1 + -3y = (-16 + 2y)
Solving
1 + -3y = -16 + 2y
Solving for variable 'y'.
Move all terms containing y to the left, all other terms to the right.
Add '-2y' to each side of the equation.
1 + -3y + -2y = -16 + 2y + -2y
Combine like terms: -3y + -2y = -5y
1 + -5y = -16 + 2y + -2y
Combine like terms: 2y + -2y = 0
1 + -5y = -16 + 0
1 + -5y = -16
Add '-1' to each side of the equation.
1 + -1 + -5y = -16 + -1
Combine like terms: 1 + -1 = 0
0 + -5y = -16 + -1
-5y = -16 + -1
Combine like terms: -16 + -1 = -17
-5y = -17
Divide each side by '-5'.
y = 3.4
Simplifying
y = 3.4

You can always share this solution

See similar equations:

| 2x+34=16+x | | 7x-3x=2(x+1) | | 15+3x-2=4 | | 4x-32=x+4 | | 3-2x+x+3=2x-1+3x+1 | | x+7+5=15+x+5 | | x+1+x-1=x-2+x+3 | | 5(3x-2)=(2x+3)/2 | | -9/1= | | 6y-4-y-4y=12-17 | | 6(x+12)=42 | | p^2+3p=q^2+3q | | 5x(3x-6x+5x)=23 | | 4x+8=3x+29 | | (52)0= | | 2(1-x)=3+x | | 3x(2x-5)-(x+7)=(x-9)(-5) | | X^8+3x^4-4=0 | | 7x-5=15-x | | 4xy-x^2=3 | | (6x+4)+(15-7x)= | | y^2+3xy-4x^2=0 | | 3(2a+1)=5(a+2) | | 2x^3+3x^2+4=0 | | 2x-7=6x+1 | | 4x+261=14x-9 | | 123-5x=13+21 | | 3(x-2y)-(x-10y)= | | 28x-3x=25 | | 2(2x+2)=20 | | -17-6x=10-9x | | 18y^2+24y+41=0 | | ln(4x-9)+ln(3)=2lnx | | 2(3x+7)+4(3x+2)=6(5x+9)+3 | | 3x+7=4+2x-9 | | 6x^2-7-11x=0 | | 5k-3(1-k)= | | (y-3)(y-3)-10(y-3)+25=0 | | 0.15x+0.07(70000-x)=6000 | | 3(n-2)=5(n+4) | | -3(x-4)=4(8-x) | | 3(x-4)=4(8-x) | | 72-3x=6x+21 | | -3(4x-5)=-9 | | 8m+15=11m | | -2(2x+3)=6 | | 6+7=30+x | | 3a+8b-3a-1b= | | 11y+10=3y-6 | | 5m-3=8m-12 | | 3y-4y-y= | | 9u+3=9l-2u | | 2x^2+8x+19=0 | | 7a+3=5a+1 | | 3a+7=2a+5 | | 12-3x=39 | | 7(x-5)=3(x+5) | | 15c^2-4c-11=0 | | 12-4a=a-3 | | 36.7=x^2-7x | | 12.25+49=x^2 | | x^2+16x=-4 | | 4[6-2(2m+1)]-7m= | | 36.7=-x^2+7x | | Y=24.5+12.25 |


Related pages


what is the prime factorization of 875what is square root of 576prime factors of 490vx 6xwhat is the prime factorization of 31finding percentage calculator0.375 as a fraction4y 3x 12converting percents to fractionshow to graph y 3xcos 2x sin x 0derivative of e ln xlog6 1senx cosxtanx dxgcf of 26vf 2 vi 2 2adderivates calculatorfactorise x 3-8square root of 1296cos 5x in terms of cos x6.25 fractionsolve y 2x 4312.23linear system solver with stepswhat is the prime factorization of 192what is the derivative of lnxprime factorization 1602x 3y 6 slopey 2cos2xprime factor tree for 542n2007solve sin2x sinx 0derivative of cos ymultiplying improper fractions calculator99 prime factorizationhow do you write 20 as a decimal820-10prime factorization 4593 roman numeralssin5x sin3x 0ln2xsquare root of 0.641.375 in fraction9x 2-4derivative of ln x squared39.99 pounds in euroswhat is the gcf of 32 and 64the prime factorization of 72prime factorization of 58sqrt 3 9ln2x derivativegcf of 46 and 69factor 3x 2 6xarcsin 2x32 qt to galgcf of 150xy 2-x 3y 60.1875 as a fractiongcf of 144multiples of 324derivative cos 3xsquare root of 75 simplifiedfactoring by grouping calculator with stepsprime factor of 441what is the prime factorization of 17548x3derivative of tan-1 xgraph x 2y 0824.8multiplication of fraction calculator3y 4xderivative of ln5x